Humanized Mouse Model as a Novel Approach in the Assessment of Human Allogeneic Responses in Organ Transplantation - Ajith, Ashwin; Mulloy, Laura L.; Musa, Md. Abu; Bravo-Egana, Valia; Horuzsko, Daniel David; Gani, Imran; Horuzsko, Anatolij (Frontiers in Immunology, 2021)
The outcome of organ transplantation is largely dictated by selection of a well-matched donor, which results in less chance of graft rejection. An allogeneic immune response is the main immunological barrier for successful organ transplantation. Donor and recipient human leukocyte antigen (HLA) mismatching diminishes outcomes after solid organ transplantation. The current evaluation of HLA incompatibility does not provide information on the immunogenicity of individual HLA mismatches and impact of non-HLA-related alloantigens, especially in vivo. Here we demonstrate a new method for analysis of alloimmune responsiveness between donor and recipient in vivo by introducing a humanized mouse model. Using molecular, cellular, and genomic analyses, we demonstrated that a recipient’s personalized humanized mouse provided the most sensitive assessment of allogeneic responsiveness to potential donors. In our study, HLA typing provided a better recipient-donor match for one donor among two related donors. In contrast, assessment of an allogeneic response by mixed lymphocyte reaction (MLR) was indistinguishable between these donors. We determined that, in the recipient’s humanized mouse model, the donor selected by HLA typing induced the strongest allogeneic response with markedly increased allograft rejection markers, including activated cytotoxic Granzyme B-expressing CD8+ T cells. Moreover, the same donor induced stronger upregulation of genes involved in the allograft rejection pathway as determined by transcriptome analysis of isolated human CD45+cells. Thus, the humanized mouse model determined the lowest degree of recipient-donor alloimmune response, allowing for better selection of donor and minimized immunological risk of allograft rejection in organ transplantation. In addition, this approach could be used to evaluate the level of alloresponse in allogeneic cell-based therapies that include cell products derived from pluripotent embryonic stem cells or adult stem cells, both undifferentiated and differentiated, all of which will produce allogeneic immune responses.